2007
DOI: 10.1080/02664760701236905
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian Inference for Skew-normal Linear Mixed Models

Abstract: Linear mixed models (LMM) are frequently used to analyze repeated measures data, because they are more flexible to modelling the correlation within-subject, often present in this type of data. The most popular LMM for continuous responses assumes that both the random effects and the within-subjects errors are normally distributed, which can be an unrealistic assumption, obscuring important features of the variations present within and among the units (or groups). This work presents skew-normal liner mixed mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
172
0
5

Year Published

2007
2007
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 146 publications
(178 citation statements)
references
References 16 publications
1
172
0
5
Order By: Relevance
“…The skew-elliptical distribution is an attractive class of asymmetric thick-tailed parametric structure, which includes the skew-normal (SN) distribution as a special case. Different versions of the multivariate SN distributions have been considered and used in the literature (Arellano-Valle et al, 2005Arellano-Valle and Azzalini, 2006;Azzalini and Capitanio, 1999;Jara et al, 2008;Sahu et al, 2003;and others). These studies demonstrated that the SN distribution has reasonable flexibility in real data fitting, while it maintains some convenient formal properties of the normal density.…”
Section: Multivariate Skew-normal Distributionsmentioning
confidence: 99%
“…The skew-elliptical distribution is an attractive class of asymmetric thick-tailed parametric structure, which includes the skew-normal (SN) distribution as a special case. Different versions of the multivariate SN distributions have been considered and used in the literature (Arellano-Valle et al, 2005Arellano-Valle and Azzalini, 2006;Azzalini and Capitanio, 1999;Jara et al, 2008;Sahu et al, 2003;and others). These studies demonstrated that the SN distribution has reasonable flexibility in real data fitting, while it maintains some convenient formal properties of the normal density.…”
Section: Multivariate Skew-normal Distributionsmentioning
confidence: 99%
“…Studies on the multivariate skew-normal distributions are also presented by (Azzalini and Dalla Valle, 1996). The skew-normal linear mixed models are presented by Arellano-Valle et al (2005), Lachos et al (2010) and Lin (2008).…”
Section: Introductionmentioning
confidence: 99%
“…In this paper, we apply the following properties of skew-normal distribution during parameter estimation of skew-normal mixed model (See [15] for more about the properties of skew-normal distribution).…”
Section: Introductionmentioning
confidence: 99%